THE EFFECT OF CREDIT RISK AND LIQUIDITY ON FINANCIAL PERFORMANCE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATING VARIABLES - I Gede Wiweka Nanda; I Gusti Ayu Eka Damayanthi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The financial performance of banking institutions is influenced by their ability to optimally manage credit risk and liquidity. This study aims to examine the effect of credit risk and liquidity on financial performance, with corporate social responsibility (CSR) as a moderating variable. The population of this research consists of banking companies listed on the Indonesia Stock Exchange during the 2021–2023 period, with a total of 93 observations. Financial performance is measured by Return on Assets (ROA), credit risk is measured by Non-Performing Loans (NPL), liquidity is measured by the Loan to Deposit Ratio (LDR), and corporate social responsibility is measured using the Corporate Social Responsibility Index (CSRI). This study adopts a quantitative approach using moderated regression analysis. The results show that credit risk has a negative and significant effect on financial performance, while liquidity has a positive and significant effect. Furthermore, CSR does not significantly moderate the relationship between credit risk and financial performance, but it is proven to weaken the effect of liquidity on financial performance in banking companies listed on the Indonesia Stock Exchange.